Alcohol consumption increases basal extracellular glutamate in the nucleus accumbens core of Sprague–Dawley rats without increasing spontaneous glutamate release. (6th June 2016) - Pati, Dipanwita; Kelly, Kyle; Stennett, Bethany; Frazier, Charles J.; Knackstedt, Lori A.
Abstract: Glutamate neurotransmission in the nucleus accumbens core (NAc) mediates ethanol consumption. Previous studies using non‐contingent and voluntary alcohol administration in inbred rodents have reported increased basal extracellular glutamate levels in the NAc. Here, we assessed basal glutamate levels in the NAc following intermittent alcohol consumption in male Sprague‐Dawley rats that had access to ethanol for 7 weeks on alternating days. We found increased basal NAc glutamate at 24 h withdrawal from ethanol and thus sought to identify the source of this glutamate. To do so, we employed a combination of microdialysis, slice electrophysiology and western blotting. Reverse dialysis of the voltage‐gated sodium channel blocker tetrodotoxin did not affect glutamate levels in either group. Electrophysiological recordings in slices made after 24 h withdrawal revealed a decrease in spontaneous excitatory postsynaptic current (sEPSC) frequency relative to controls, with no change in sEPSC amplitude. No change in metabotropic glutamate receptor 2/3 (mGlu2/3) function was detected as bath application of the mGlu2/3 agonist LY379268 decreased spontaneous and miniature EPSC frequency in slices from both control and ethanol‐consuming rats. The increase in basal glutamate was not associated with changes in the surface expression of GLT‐1, however, a decrease in slope of the no‐net‐flux dialysis function was observed following ethanol consumption, indicating a potential decrease in glutamate reuptake. Taken together, these findings indicate that the increase in basal extracellular glutamate occurring after chronic ethanol consumption is not mediated by an increase in action potential‐dependent glutamate release or a failure of mGlu2/3 autoreceptors to regulate such release. Abstract : Upon finding an increase in nucleus accumbens basal glutamate following intermittent access to alcohol in the Sprague–Dawley rat, we sought to identify the source of this glutamate. We employed microdialysis, electrophysiology and western blotting to examine the potential role of known presynaptic and glial sources of glutamate. Our results indicate that increased basal glutamate following alcohol consumption does not arise from a loss of function of presynaptic autoreceptors or an increase in sodium‐channel mediated release, nor does it strengthen excitatory synapses, as we found no change in excitatory postsynaptic frequency or amplitude.